BOOK REVIEWS (Historia, 2021)
1. RICHARD ELPHICK and HERMAN GILIOMEE (eds.)The shaping of South African society, 1652-1840 (2nd edition) 2. BERNARD LUGANHistoire de l~frique du Sud de l'Antiquitea nosjours 3. M. SIENAERT-VAN REENENDie Franse bydrae tot Africana-literatuur 1622-1902 4. B.J.T. LEVERTON (ed.)Record of Natal, Volume Two, September 1828 - July 1835 5. ROGER C. FISHER en SCHALK LE ROUX (samestellDie Afrikaanse Woning: hedrukke uit 'Die Boerevrou' 6. GEORGE HOLMES (red.)The Oxford Rlustrated history of Medieval Europe